ANALISIS SIKAP SISWA TERHADAP NORMA SOSIAL DI SMPN 7 SATU ATAP PUJUD - Hayati, Nur Hayati Nur; Yakub, Elni Yakub Elni; Saam, Zulfan Saam Zulfan (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstrak : The method used in this research is the method Quasi experiment, the population in this study were students of class VII, VIII, IX SMP 07 Satu Atap Pujud and a sample of 100% of the total population by using simple technical rendem sampling. (1) The description of students attitudes toward social norm  for SMP 07 Satu Atap Pujud. Largely have shown a positive attitude towards social norms and there is a small part that is negative to the social norms. Examples being negative is often grumble to parents when in advise, laughings, as a daughter not dating until late at night, as the girls do not wear tight clothes, for example pencil pants and short shirts. (2) Description of the background of social norms is the level of parental education and occupation of parents. The level of parental education is the dominant elementary / junior declared the value of the character of social norms whereas, higher education levels maintain coorperation, job dominant parents are farmers declared the values of the character of social norms while, work entrepreneur maintain cooperation. (3) Description of students attitudes toward social norms in terms of ethnic Jvanese and Batak in SMP 07 Satu Atap Pujud ethnic Javanese show greater understanding of social norms compared with the ethnic Batak.Norms that exist in the school and in the community recommendation is : (1) Prior to conducting research inin can be seen that the students do not understand about the social norms that exist in the school and community environment for it to the school SMP 07 Satu Atap Pujud to be able to pay attention students in the act. (2) After the conducted research there are many students who are already a ware of the social norms for the BK teachers in SMP Satu Atap Pujud in order to provide an understanding of the norms that exist. (3) To further research in order to examine  the norms that others can seen other differences. Keywords: students attitudes toward social norms.